The crystal structure of N-(6-chloro-2-methyl-2H-indazol-5-yl)acetamide, C10H10ClN3O - Du Yi-Jing; Sun Hong-Shun; Wang Jian-Qiang; Guo Cheng (Zeitschrift für Kristallographie - New Crystal Structures)
C10H10ClN3O, monoclinic, P21/c (no. 14), a = 4.7273(7) Å, b = 10.2148(16) Å, c = 21.283(3) Å, β = 91.458(4)°, V = 1027.4(3) Å3, Z = 4, Rgt ${R}_{gt}$ (F) = 0.0623, wRref $wR_{ref}$ (F 2) = 0.1287, T = 193 K.